2013
DOI: 10.1007/s40256-013-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylcysteine on the Cardiac Remodeling Biomarkers and Major Adverse Events Following Acute Myocardial Infarction: A Randomized Clinical Trial

Abstract: NAC can be beneficial in preventing early remodeling by reducing the level of MMP-2 and MMP-9. Moreover, NAC decreased the length of hospital stays in patients after AMI. By decreasing MACE, NAC could possibly be introduced as a 'magic bullet' in the pharmacotherapy of patients with AMI. Further studies are needed to elucidate NAC's role in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
9
0
3
Order By: Relevance
“…Moreover, NAC can also inhibit maladaptive autophagy, which promotes the pathogenesis, in pressure overload-induced cardiac remodeling in rats [101]. The role of NAC has also been validated in the myocardial infarction patients, although these results need to be further explored in a larger population [102]. Vitamin E is another antioxidant with the clinical potential to the treatment of cardiovascular diseases.…”
Section: Anti-ros Systems and Clinical Applicationmentioning
confidence: 99%
“…Moreover, NAC can also inhibit maladaptive autophagy, which promotes the pathogenesis, in pressure overload-induced cardiac remodeling in rats [101]. The role of NAC has also been validated in the myocardial infarction patients, although these results need to be further explored in a larger population [102]. Vitamin E is another antioxidant with the clinical potential to the treatment of cardiovascular diseases.…”
Section: Anti-ros Systems and Clinical Applicationmentioning
confidence: 99%
“…33) Talasaz, et al also found that NAC may help reduce levels of MMP-2 and MMP-9. 13) A total of 9 RCTs were included in this metaanalysis and all subjects had STEMI. After the analysis, it was found that all-cause mortality and MACE occurrence in the NAC group were significantly lower than in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Randomization was mentioned in all studies. However, 8 studies [8][9][10][11][12][13]15,16) expounded the generation of random sequences. Only one study 8) described allocation concealment.…”
Section: Basic Information Of the Included Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal, Talasaz et al [25] once again address the efficacy of NAC to control post-MI remodeling. They suggest that NAC could improve the myocardial remodeling following AMI in a proof-ofconcept clinical trial.…”
mentioning
confidence: 99%